Bothered and bewildered, but not bewitched - Ushma S. Neill; Laurence A. Turka (The Journal of Clinical Investigation, 2008)
Unfortunately, we seem to run article amendments (corrections, errata, retractions, addenda) in every issue these days. In the current issue, we have a correction and a retraction — both coming after intensive investigations and peculiar situations we hadn’t encountered before.